Strategi Dakwah MGT Radio Bandung pada Program Pintu Hikmah - Abdul Basith Muhammad; Neneng Faoziyah; Hani Hadiati Pujawardani (IAIN Madura, 2024)
This research is backgrounded by the importance of media and strategy in the implementation of da'wah. The objectives of this study are; 1) to identify and describe the da'wah strategy used in the Pintu Hikmah program at MGT Radio Bandung, 2) to find out the supporting and inhibiting factors in the Pintu Hikmah program at MGT Radio Bandung. The research approach uses a qualitative approach descriptive method. Data collection techniques with interviews, observation, and documentation studies. The results of this study indicate 1) the da'wah strategy on the Pintu Hikmah program uses da'wah bil-lisan by formulating a strategy, namely by determining the concept of da'wah by broadcasting hadith and religious songs on the Hikmah program. The implementation of the Pintu Hikmah program is broadcast every day for one hour with hadiths that have been prepared for 1 month broadcasting, strategy evaluation is carried out at the end of the program. The Pintu Hikmah program has a differentiator from other radio da'wah programs by including religious songs after the end of hadith broadcasting, with a different concept it can attract listeners and make people curious about what will be presented. As a result, the quantity of listeners of Pintu Hikmah program every day is stable listened by 9,000-11,000 listeners. 2) Supporting factors in the Pintu Hikmah program are the placement of the program time before the main program so that listeners are interested, while the inhibiting factor is the unavailability of preachers who meet the predetermined criteria standards to fill the Pintu Hikmah program.